2012
DOI: 10.1002/prot.24163
|View full text |Cite
|
Sign up to set email alerts
|

Comparing aminoglycoside binding sites in bacterial ribosomal RNA and aminoglycoside modifying enzymes

Abstract: Aminoglycoside antibiotics are used against severe bacterial infections. They bind to the bacterial ribosomal RNA and interfere with the translation process. However, bacteria produce aminoglycoside modifying enzymes (AME) to resist aminoglycoside actions. AMEs form a variable group and yet they specifically recognize and efficiently bind aminoglycosides, which are also diverse in terms of total net charge and the number of pseudo-sugar rings. Here, we present the results of 25 molecular dynamics simulations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 102 publications
2
11
0
Order By: Relevance
“…In this predicted model a short distance between an amino acid and the inhibitor is an indicator of interaction strength. As it can be seen in Figure 2, amino acids D115 and D152 are near the inhibitor molecule, which agrees with results obtained by X-ray crystallography of AAC(6′)-Ib complexed to kanamycin C and acetyl CoA 21 and by molecular dynamics simulations 29 .…”
supporting
confidence: 89%
“…In this predicted model a short distance between an amino acid and the inhibitor is an indicator of interaction strength. As it can be seen in Figure 2, amino acids D115 and D152 are near the inhibitor molecule, which agrees with results obtained by X-ray crystallography of AAC(6′)-Ib complexed to kanamycin C and acetyl CoA 21 and by molecular dynamics simulations 29 .…”
supporting
confidence: 89%
“…A coordinated dynamics may be more important instead, which may separate these two enzymes. Consistent with these data, a recent computational work also suggested that dynamics of each AGME and their interactions with the same AG may be different …”
Section: Discussionsupporting
confidence: 55%
“…4c; see below). The negative charge may mimic the nucleic acid environment that the aminoglycosides bind to in the ribosome (Romanowska et al, 2013) and is required for binding of the positively charged drug molecules.…”
Section: Ligand-binding and Catalytic Sites Of Aadamentioning
confidence: 99%